Effect of glyphosate on banana growth and yield. - Agüero, Renán (2016)
The objective of this study was to determine the effect of successive use of glyphosate - sprayed as recommended by the manufacturer - in banana growth and yield. The experiment started in November, 1996 at the San Pablo farm located in the Atlantic region of Costa Rica. Production units at a similar phenological stage (al1 of them showing grandmother-mother-son) were ramdomly chosen. Several treatments with glyophosate were analyzed on said units, ranging from one application to consecutive-application cycles every seven weeks. A control - hand-weeded once a month - was included. The treatments evaluated did not affect the diameter of pseudostems, plant height, number of leaves, width of youngest leaf, or root weight of sprayed sons. Likewise, growth synchronization between mothers and sons, as wel1 as fruit yield and quality, were not affected.